PELATIHAN PENYUSUNAN LAPORAN KEUANGAN UMKM ANGKRINGAN DAERAH JAGAKARSA JAKARTA SELATAN - Salwa, Shifa Ashila; Elok , Galuh Putri; Putri , Adelia; Nursyiah , Lely Salsabila; Rahmadi, Zara Tania; dharma , Dias Adi (ASOSIASI IDEBAHASA KEPRI, 2025)
This initiative aims to provide training for Angkringan MSME (Micro, Small, and Medium Enterprise) owners in Jagakarsa, South Jakarta, on preparing simple financial reports. The objective is to enhance their ability to manage their businesses more effectively by implementing proper financial recording practices. The community service program consists of several stages, including field observations, interactive discussions, financial report preparation training, and evaluation of the training outcomes. The primary participant in this activity is the owner of Angkringan Ways, with the training scheduled to take place in December 2024. The training significantly improved participants' understanding of financial recording. They began to adopt better financial management practices, such as separating personal and business finances. Additionally, they started using standardized financial report formats, including general journals, ledgers, and income statements, to keep track of their business transactions systematically. This program has had a positive impact on enhancing MSME owners' financial management skills. With continued mentoring, it is expected that systematic financial recording will be consistently implemented, contributing to the long-term sustainability of their businesses.